Evaluation of in Vitro Fertilization Index by Caudal Spermatozoa Capacitation with Different Heparin Concentration in Iraqi Sheep: Wafir Mahdi Saleh and Ali Abdul-Ameer - Saleh, Wafir Mahdi (The Iraqi Journal of Veterinary Medicine, 2019)
Sperm capacitation refers to the physiological changes in which spermatozoa must undergo in order to have its ability to penetrate and fertilize a mature oocyte. Recognition of the phenomenon was quite important to early in vitro fertilization (IVF) experiments as well as to the fields of embryology and reproductive biology. This initial study is designed to study the process of capacitation of ram sperm with three heparin levels (50,100,150 IU). 140 pairs of abattoir testicular samples (70 pairs each season), with 70 ewe genitalia specimens (35 each season). Spermatozoa sample were capacitated with heparin in CO2 incubator for 45 minutes, and evaluated by its total motility and its ability to penetrate oocytes zona pellucida for fertilization. Different heparin level for spermatozoa capacitation in relation to seasonal influences revealed that; in regarding to capacitation index there was an increased spermatozoa activity and motility significantly for the three levels within season, but capacitation index showed significant variations between the three heparin levels out of breeding season in which the highest heparin level gave the best capacitation index than the other two. Results of oocytes collection in relation to seasonal influences revealed to; total oocytes number was 2035 oocytes on both season in which 1039 oocytes were obtained within season while a number of 1006 oocytes was collected out of season. Oocytes maturity index within season time is about 40% for the oocytes grade V.good and good grade, fair and poor grade is 25%.Oocytes collected out of breeding time showed range between 25% for the v. good and good grade to 10% for the other. Fertilizable index for embryos development after capacitated spermatozoa adding to the medium containing matured oocytes is range from 35% for the v. good and good graded oocytes within a season to 10% out of season. In conclusion; heparin can induced spermatozoa capacitation in any levels through the breeding season while the high level of heparin gave better results, fertilizable index and embryo production are both gave best result via breeding season.